The Effect of Green Marketing on Lebanese Consumer Behavior in Retail Market - Hussein, Said; chams, Mayssa (British Journal of Marketing Studies, 2017)
Green marketing is appreciated for being the marketing of products that are presumed to be environmentally safe. This new concept which aims to modify and improve the behavior of consumers is widely discussed these days with a primary purpose of environmental protection. The intention of this study was to investigate the relationship between consumer’s behavior and the associated environmental problems and green marketing challenges. Data analysis produced from a consumer survey in Lebanon testing the socio demographic and the external factors affecting the customer behavior, demonstrated a high level of awareness toward the importance of protecting the environment and its resources, additionally, it showed a great responsibility from the part of the Lebanese consumers who expressed their willingness to behave in a responsible manner through their involvement in ecological actions.